Character Education di Indonesia: Menguak Pemikiran Pendidikan K.H. Hasyim Asyâari - Mukani, Mukani (Program Pascasarjana UIN Sunan Ampel Surabaya, 2007)
Modernization has indeed brought about a significant change in education. Inresponse to it, education has reoriented itself in terms of its curriculum, teachingmethodology, teaching qualification, institution management, leadership managementand so on. In Indonesia efforts to modernize education are still limited to what seems tobe the mere surface of the matter. These efforts in other words, do not deal as yet withthe substance ânamely the philosophical aspect- of education. KH. Hasyim Asyâari however,is an exception. Having been thought of as a traditional scholar, he nonetheless wascapable of providing insights that might lead to a dynamization and modernization ofeducation in Indonesia. His thoughts are highly relevant to the issue of educational reform.Given that his ideas are largely conceptual and philosophical, a study that concerns itselfwith this area of investigation must pay an attention not only to his intellectual corpus butalso to those technical and operational issues that have to do with this corpus. In this waywe will have a comprehensive and balanced view of education; a view that entertains thebelief that education is there to produce man of both knowledge and morality, man thatboth knows and obeys the norms and values of society.